THE OPTIMIZATION OF BILATERAL INVESTMENT TREATY TO ENCOURAGE THE DEVELOPMENT OF MICRO SMALL AND MEDIUM ENTERPRISES IN INDONESIA AS HOST STATE IN INTERNATIONAL INVESTMENT ACTIVITIES - Imanuddin, Sabrina Aqila (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2023)
International investment can accelerate economic growth and accelerate development in Indonesia. The Bilateral Investment Treaty (BIT) is an international agreement between two countries on provisions for international investment. The BITs are intended to promote the development of micro, small and medium enterprises in the country. Again, Small and medium-sized enterprises (SMEs) in Indonesia need support in promotion and legal protection to develop and become more optimal, as SMEs are the backbone of the Indonesian economy and part of the implementation of the Pancasila economic system. SMEs development provisions can be addressed in international agreement such as BIT or Free Trade Agreements (FTA) to provise a forum for broader sectors that include SMEs. Therefore, to develop SMEs in Indonesia through international investment practices, it is necessary that related parties, i.e., the government to take measures for optimizing the development of SMEs in Indonesia and obtain comprehensive international investment support to strengthen through International Investment Agreements (IIA) and be competitive in the global market through strengthening and broadening the scope of SMEs in IIA.